Need Analysis for the Development of a Braille Early Reading Skills Teaching Module for Preschool Children with Visual Impairment - Awang, Azizah; Abdul Rani, Intan Farahana; Kway , Eng Hock (Jurnal Pendidikan Bitara UPSI, 2024)
For module design and development studies, a needs analysis study is very important to explore the needs of teachers as module users. This study aims to explore the need to develop a braille early reading skills teaching module for children with visual impairment preschool. This needs analysis was conducted on four special education preschool teachers with disabilities at the Ministry of Education Malaysia. Data collection was conducted using semi-structured interview method to obtain insights and ideas in teaching braille early reading skills based on Discrepancy Model McKillip. The findings identified four main objectives: (1) challenges during the teaching of Braille early reading skills; (2) methods of teaching braille early reading skills; (3) development needs of braille early reading skills module and (4) characteristics of braille early reading skills module. The findings of this needs analysis indicate that the Braille early reading skills module has a need to be developed to overcome the challenges faced by preschool teachers in teaching braille early reading skills. This study is also expected to assist researchers in the production of quality modules and to solve the challenges faced by teachers in teaching braille early reading skills for preschool children. This is in line with Sustainable Development Goal 4 (SDG 4) which promotes quality and equitable inclusive education for all children.